PUNISHMENT, INTEGRATION, FORGETTING. POST-WAR FATE OF MUSLIMS FROM STARA RAŠKA MEMBERS OF THE GERMAN FORCES IN WWII (Heritage, 2024)
This is a story about an episode from the past of Bosniaks in Serbia that has not been mentioned much so far, at least when it comes to domestic historiography. It refers to all those who were in the ranks of the armed forces of the Third Reich during the WWII. Emphasis is placed on their post-war destinies, i.e. their (non)punishment for collaboration and (non)integration into Yugoslav society, that is, a kind of mimicry in which the majority enter while waiting for a more favorable historical moment. Consideration of the positions of the YCP, as a decisive factor in all of this, occupies one of the key places of our research.
Keywords: Muslims, Stara Raska, Germans, Waffen-SS, Division